Climatic characteristics and their relationship to the cultivation and production of rice crop in Najaf Governorate - محمود السميع; عبد الكاظم الحلو (آداب الكوفة, 2013)
Rice is one of the most important summer grain crops in Iraq, and comes second in nutritional importance after wheat. Because of the nutritional and economic importance of rice in Iraq, and given that Najaf governorate comes at the forefront of Iraqi governorates in terms of the cultivated area and the amount of production, and what its production can lead to achieving a reasonable amount of food security, which today has become a preoccupation for many researchers. The researchers influenced his study by examining the most important climatic characteristics affecting the cultivation and production of rice, and identifying the levels of its production at the level of Iraq, as well as the geographical distribution of the main production areas in the province.